PENGEMBANGAN DAKWAH MAJELIS TAKLIM AN-NISA DI DESA BEWA KECAMATAN LORE SELATAN KABUPATEN POSO - Cikka, Khairuddin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
This paper discusses Majelis Taklim (Islamic Study Group) An-Nisa located in Bewa Village, South Lore, District of Poso. Since its establishment in 1995 until now, Majelis Taklim An-Nisa has contributed a lot to the development of da’wah (Islamic propagation) in Poso, especially in Bewa village. This Majelis Taklim is supported by the government, especially the Ministry of Religious Affairs, and local communities. One of the most important contributions from Majelis Taklim is guiding mothers who converted to Islam after the Poso conflict in 1998-2000. Nevertheless, this Majelis Taklim also has obstacles in carrying out its da’wah activities, which include transportation, inadequate communication, and a lack of preachers.